Extremist identity creation through performative infighting on Steam - Newhouse, Alex Bradley; Kowert, Rachel (Frontiers in Psychology, 2025)
The video game marketplace Steam has long hosted a lively social network for the purpose of connecting game players and game developers. Over the past 5 years, however, neo-fascist and neo-Nazi communities have begun using Steam's community features to build large-scale socialization and identity creation networks. These networks, while insular, involve large numbers of Steam groups and users, who share hateful and violent content with one another. In addition, these same users frequently spread extreme messages on more public-facing content, including in game reviews and game forums. Using open-source data and scaled social network analysis, we show that the far-right ecosystem on Steam possesses characteristics of collective radicalization and mobilization. This poses both an immediate danger to gamers and game developers who rely on Steam and also a longer-term risk to social safety.